Avaliação do risco de Morte Súbita Cardíaca em doentes com miocardiopatia hipertrófica - Comparação das directrizes Europeias e Americanas - Pedro Lucas Oliveira Castro (2022)
Hypertrophic cardiomyopathy (HCM) is a structural disease of the myocardium that results in cardiac functional impairment. This condition is in most cases an autosomal dominant hereditary disease with variable penetrance that can be silent until advanced ages (> 60 years) or give rise to symptoms associated with left ventricular hypertrophy in pediatric ages. Since sudden cardiac death (SCD) is one of the most devastating outcomes in patients with this disease, there is a need for risk stratification for the decision to place implantable cardioverter-defibrillators (ICDs), which are the only prognostic modifiers in high-risk patients. This narrative review presents a current perspective on HCM as well as a comparison between European and American guidelines regarding SCD risk stratification. The analysis of the studies points to a discrepancy between the two guidelines regarding the risk stratification of SCD in HCM patients, which implies a different approach in patients with this condition, with an impact on the selection of candidates for ICD placement. According to the most recent evidence, especially the results obtained by cardiac magnetic resonance imaging (CMR), it seems necessary to update the European guidelines in order to improve the agreement between the two guidelines and thus reduce the percentage of "unprotected" HCM patients with high SCD risk.